2021
DOI: 10.1111/maps.13664
|View full text |Cite
|
Sign up to set email alerts
|

Association of silica phases as geothermobarometer for eucrites: Implication for two‐stage thermal metamorphism in the eucritic crust

Abstract: Silica mineral is present in different stable polymorphs depending on the temperature and pressure conditions of crystallization. We suggest using silica mineral phases to constrain the thermal history of eucrites. We focused on silica minerals in basaltic clasts of nine non-cumulate eucrites to compare with previously studied cumulate eucrites. Our observations indicate an apparent relationship between thermal metamorphic degrees and silica phase texture in basaltic clasts of non-cumulate eucrites. To reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…In particular, we have shown that cristobalite can crystallize at temperatures well below 1470°C in a system with SIR bulk chemistry. Ono et al (2021) also observed primary cristobalite in experiments on a eucrite composition, during cooling at rates of 0.1-1°C h À1 from peak temperatures 1250-1300°C. In addition, the origin of tridymite in the rim on EET 92042 Ch11 is not clear.…”
Section: Petrographic Constraints On Sir Formation Conditionsmentioning
confidence: 68%
See 4 more Smart Citations
“…In particular, we have shown that cristobalite can crystallize at temperatures well below 1470°C in a system with SIR bulk chemistry. Ono et al (2021) also observed primary cristobalite in experiments on a eucrite composition, during cooling at rates of 0.1-1°C h À1 from peak temperatures 1250-1300°C. In addition, the origin of tridymite in the rim on EET 92042 Ch11 is not clear.…”
Section: Petrographic Constraints On Sir Formation Conditionsmentioning
confidence: 68%
“…Ono et al. (2021) also observed primary cristobalite in experiments on a eucrite composition, during cooling at rates of 0.1–1°C h −1 from peak temperatures 1250–1300°C. In addition, the origin of tridymite in the rim on EET 92042 Ch11 is not clear.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations